Muhammadiyah University of Luwuk Volleyball UKM Students' Overhead Pass Training Model - Bakar, Abu; Gui, Jamaludin Bahtiar; Nur, Ardiansyah (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objectives. overhead passing training model for Volleyball UKM students . Materials and Methods. The research method used is research and development ( R &D). namely combining qualitative and quantitative methods which adopt the ADDIE development design consisting of The 5 stages are: (1) Analysis (2) Design (3) Development (4) Implementation (5) Evaluation. The instrument used to collect data is an assessment questionnaire. Results. Assessment of the Feasibility of the Volleyball Overhead Passing Training Model with the development carried out, namely adding concepts in the application of Overhead Passing Training, seen from the results of the material expert validator of 93.75% (feasible) and the media validator of 96.25% (feasible). Conclusions. Based on the results obtained, the Development of the Upper Passing Model is good to be used as a training model in the Volleyball UKM of Musamus University, Merauke.